Investigating the heat distribution on welded parts from a TIG welding operation in a railcar manufacturing environment. Issue 1 (31st December 2022) - Seloane, Walter Thabo; Mpofu, Khumbulani; Ramatsetse, Boitumelo; Modungwa, Dithoto
Abstract: Dedicated welding fixtures have been utilized in the railcar manufacturing industry to stabilize welded parts during welding-assembly processes. The use of this fixture results in poor quality and repeatability of welded parts, as well as reduced versatility amongst components and storage problems. The intelligent reconfigurable welding fixture (IRWF) was therefore developed to mitigate the problems encountered in the railcar manufacturing environment. This paper presents the heating-analysis study conducted on the welding fixture components to evaluate the transient heat distribution during the welding of stainless steel 316 components using both an experimental and a finite element analysis approach. In addition the temperature distribution on welded components during a Tungsten Inert Gas (TIG) welding operation was analysed. The TIG welding experiment was first conducted to generate data that served as input during the Finite Element Analysis (FEA) study. A Thermographic camera was used to measure the heat distribution across welded parts immediately after welding. Solid edge FEA was used to conduct a sequential numerical simulation analysis of the thermal heating effects on stainless steel. Thermocouples were embedded in the fixture blocks of the respective welding stations to measure the heat generated on the fixture during welding. The heat analysis study conducted on the fixture using thermocouples yielded very good results. It was successfully proven using experiments that the fixture was exposed to a temperature of less than 30°C during welding. The numerical simulation conducted on welded parts during TIG welding showed a maximum temperature distribution of 309°C.